2003
DOI: 10.1021/om0302894
|View full text |Cite
|
Sign up to set email alerts
|

Halogen-Substituted 2,6-Bis(imino)pyridyl Iron and Cobalt Complexes:  Highly Active Catalysts for Polymerization and Oligomerization of Ethylene

Abstract: A series of halogen-substituted 2,6-bis(imino)pyridyl ligands and their iron and cobalt complexes [{2,6-(2,6-X1X2C6H3NCCH3)2C5H3N}MCl2] (X1 = X2 = Br, M = Fe (1), Co (2); X1 = X2 = Cl, M = Fe (3), Co (4); X1 = Cl, X2 = H, M = Fe (5), Co (6); X1 = Br, X2 = H, M = Fe (7), Co (8); X1 = I, X2 = H, M = Fe (9), Co (10)) and [M{2,6-(2,6-X1X2C6H3NCCH3)2C5H3N}2]2+[MCl4]2- (X1 = F, X2 = H, M = Fe (11)) have been synthesized. The molecular structures of complexes 1, 8, 9, 10, and 11 were determined by X-ray diffraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(101 citation statements)
references
References 32 publications
9
92
0
Order By: Relevance
“…45, 54 Complexes with only one fluoro substituent at the imino-N aryl ring ortho position had the highest oligomerization activity. The introduction of an electron withdrawing group could increase the electrophilicity of the central metal Fe and the coordination of ethylene, favoring the 60 catalytic activity.…”
Section: Bis(imino)pyridine Type Ligationmentioning
confidence: 99%
“…45, 54 Complexes with only one fluoro substituent at the imino-N aryl ring ortho position had the highest oligomerization activity. The introduction of an electron withdrawing group could increase the electrophilicity of the central metal Fe and the coordination of ethylene, favoring the 60 catalytic activity.…”
Section: Bis(imino)pyridine Type Ligationmentioning
confidence: 99%
“…Another effective strategy is the tuning of the electronic state of the complexes. Qian et al reported that the steric bulk and electro-withdrawing property of the halogen substituents have significant effects on the catalyst activity and the molar mass of the product [15] [16]. The charge control of the metal center in the complex could be achieved by introducing electro-donating groups or electro-withdrawing groups [17] [18] [19].…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic performances have been greatly improved by introducing halogen atoms into ligands [5,6], and anew method for synthesis of halogen substituted bis(imino)pyridines hasbeen reported [7]. The title compound is in the E conformation.…”
Section: Discussionmentioning
confidence: 99%